Cross-cultural adaptation and validation of the Spanish version of the Orthognathic Quality of Life Questionnaire for patients with dentofacial deformities. Issue 12 (December 2020) - Duarte, Valentina; Zaror, Carlos; Villanueva, Julio; Werlinger, Fabiola; Vidal, Constanza; Solé, Pedro; O'Ryan, Juan Alberto; Corona, Gastón; Dallaserra, Matías; Moreno, Begoña; Muñoz, Maximiliano; Cuellar, Javier; et al.
Abstract: Objective: The aim of this study was to develop a Spanish version of the Orthognathic Quality of Life Questionnaire (OQLQ) that is conceptually equivalent to the original questionnaire, as well as acceptable, reliable, valid, and responsive for use in Chilean patients with dentofacial deformities. Material and methods: The recommended standard methodology, with direct and back-translation, was used. A prospective longitudinal multicenter study of adult patients diagnosed with dentofacial deformity was carried out, self-administrating OQLQ, OHIP-14 (Oral Health Impact Profile), and SF-36 (Short Form 36 Health Survey) during the presurgery visit in order to examine construct validity. To evaluate reproducibility, questionnaires were re-administered 4 weeks later to subjects with a stable dental condition. Responsiveness was assessed among subjects followed up until 3 months after surgery. Results: Of the 230 patients under presurgical orthodontic treatment included in the study, 216 completed the questionnaire, 142 formed the reliability sub-sample, and 30 were evaluated 3 months after surgery. Cronbach's alpha ranged from 0.78 to 0.94 and test–retest intraclass correlation coefficients ranged from 0.84 to 0.91 ( p = 0.001) by dimension. The correlation matrix between OQLQ dimensions and SF-36 and OHIP-14 confirmed most of the associations previously hypothesized as moderate (rs > 0.4). Confirmatory factor analysis supported the same structure as the original instrument, considering four dimensions. Responsiveness was demonstrated by the large improvement observed in the global score 3 months after surgery: mean change ±SD = −15.1 ± 18.05 and standard response mean = −0.84 ( p < 0.001). Conclusions: The Spanish version of OQLQ has demonstrated good levels of reliability, validity, and responsiveness – similar to those of the original questionnaire.